The Importance of Fluctuating Asymmetry as an Indicator of Environmental Stress: Wing Morphological Responses of Euglossa melanotricha to an Altitudinal Gradient - Marcela Vaca-Sánchez; Pablo Cuevas-Reyes; Icauri Prieto-Dueñas; Israel Munck; Yumi Oki; Kamilla Castelan; Geraldo Wilson Fernandes (Sociobiology)
Abrupt abiotic changes in mountain ecosystems act as environmental filters, influencing the phenotypic expressions of numerous organisms. On the other hand, these responses along altitude gradients for native species are little understood. In this work, we examined the alterations in wing morphology, wing size, and vein fluctuating asymmetry (FA) of Euglossa melanotricha (Apidae: Euglossini) in relation to climatic variables across an altitudinal gradient in the rupestrian grassland (campo rupestre) of Serra do Cipó, Brazil. For this, we collected at each altitude point  (1. 800 m; 2. 900 m; 3. 1000 m; 4. 1100 m; 5. 1200 m; 6. 1300 m; 7. 1400 m) a total of 20 individuals of E. melanotricha. A significant difference was identified in E. melanotricha wing veins fluctuating asymmetry along the altitudinal gradient where the higher values were recorded in sites at higher altitudes. Contrary, we found that wing area, wing length and wing width presented higher values in sites at lower altitudes. In relation to wing morphology, the larger and wider wings were recorded in sites at lower altitudes in comparison with sites at higher altitudes, where wings were narrower and less elongated. The results of this study demonstrate that changes in climatic conditions along the altitudinal gradient have a significant impact on the physical characteristics of E. melanotricha. Furthermore, it can be concluded that both FA and geometric morphometrics are valuable tools for monitoring environmental stress in pollinators.